2010
DOI: 10.1074/jbc.m110.100602
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Basis for the Scaffolding Role of the p50/Dynamitin Subunit of the Microtubule-associated Dynactin Complex

Abstract: p50/dynamitin (DM) is a major subunit of the microtubuleassociated dynactin complex that is required for stabilization and attachment of its two distinct structural domains, namely the Arp1 rod and the shoulder/sidearm. Here, we define the determinants of p50/DM required for self-oligomerization of the protein and for interactions with other subunits of the dynactin complex. Whereas the N-terminal 1-91-amino acid region of the protein is required and sufficient for binding to the Arp1 rod, additional determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…A later report indicated that AA 100–403, a fragment that contains all these motifs, did not cause organelle or spindle derangement when overexpressed (Jacquot et al ., 2010). We, too, found that overexpression of TAP-tagged dynamitin AA 100–403 did not trigger release of p150 Glued or endogenous dynamitin from the Arp filament and further observed that AA 100–403 did not cosediment with Arp1 when cytosols were subjected to sucrose gradient centrifugation (Supplemental Figure S2), suggesting that this fragment cannot bind the dynamitin protomers that are incorporated into dynactin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A later report indicated that AA 100–403, a fragment that contains all these motifs, did not cause organelle or spindle derangement when overexpressed (Jacquot et al ., 2010). We, too, found that overexpression of TAP-tagged dynamitin AA 100–403 did not trigger release of p150 Glued or endogenous dynamitin from the Arp filament and further observed that AA 100–403 did not cosediment with Arp1 when cytosols were subjected to sucrose gradient centrifugation (Supplemental Figure S2), suggesting that this fragment cannot bind the dynamitin protomers that are incorporated into dynactin.…”
Section: Resultsmentioning
confidence: 99%
“…However, fragments lacking some or all of these motifs are sufficient for disruption (Maier et al ., 2008; Jacquot et al ., 2010), indicating that dynamitin may be able to trigger dynactin disassembly via more than one mechanism. In the present study, we used direct protein–protein binding assays to characterize interactions between dynamitin's N-portion and the self-associating C-terminal portion with other dynactin subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with partner proteins and oligomerization sites reported up to now are situated in the NtD2 [38,39]. The Cterminus of the protein seems to be indispensable for correct functioning of dynamitin, even though the role of this part of dynamitin remains obscure [38].…”
Section: Interactionsmentioning
confidence: 95%
“…To genetically interfere with microtubule function we ovexpressed dynamitin and disrupted dynein function (Fig. S2A) (14,15). We observed a 75% decrease in the number of structures that rotated and a 50% decrease in the speed of movement (Fig.…”
Section: Rotational Motion Occurs During Early Stages Of 3d Morphogenmentioning
confidence: 96%